2023
DOI: 10.3390/molecules28124864
|View full text |Cite
|
Sign up to set email alerts
|

NMR-Based Metabolomic Study on Phaseolus vulgaris Flour Fermented by Lactic Acid Bacteria and Yeasts

Abstract: In recent years, fermented foods have attracted increasing attention due to their important role in the human diet, since they supply beneficial health effects, providing important sources of nutrients. In this respect, a comprehensive characterization of the metabolite content in fermented foods is required to achieve a complete vision of physiological, microbiological, and functional traits. In the present preliminary study, the NMR-based metabolomic approach combined with chemometrics has been applied, for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 42 publications
(44 reference statements)
0
1
0
Order By: Relevance
“…The level of LC decreased the level of WSC in the mixed silages, which explains the reduction in LA, perhaps because there was less substrate available for LAB. Tatulli et al (2023) reported that when the WSC content was limited, heterofermentative LAB tended to be active, and several homofermentative strains such as Lactobacillus plantarum could carry out the lactic lactate/acetate conversion [49]. Keles and Demirci (2011) found that inoculation with a heterofermentative LAB (Lactobacillus buchneri) resulted in silage with higher (p < 0.05) concentrations of acetic and propionic acids and lower concentrations of LA and WSC.…”
Section: Fermentation Characteristics Of Ss-lc Mixed Silagesmentioning
confidence: 99%
“…The level of LC decreased the level of WSC in the mixed silages, which explains the reduction in LA, perhaps because there was less substrate available for LAB. Tatulli et al (2023) reported that when the WSC content was limited, heterofermentative LAB tended to be active, and several homofermentative strains such as Lactobacillus plantarum could carry out the lactic lactate/acetate conversion [49]. Keles and Demirci (2011) found that inoculation with a heterofermentative LAB (Lactobacillus buchneri) resulted in silage with higher (p < 0.05) concentrations of acetic and propionic acids and lower concentrations of LA and WSC.…”
Section: Fermentation Characteristics Of Ss-lc Mixed Silagesmentioning
confidence: 99%